Benchmarking diet quality to assess nutritional risk in hemodialysis patients: applying adequacy and moderation metrics of the hemodialysis-healthy eating index - Sualeheen, Ayesha; Khor, Ban-Hock; Balasubramanian, Gaiyal Villy; Sahathevan, Sharmela; Chinna, Karuthan; Mat Daud, Zulfitri Azuan; Khosla, Pramod; Abdul Gafor, Abdul Halim; Karupaiah, Tilakavati; Cheak, Bee Boon; Ahmad, Ghazali; Leong, Goh Bak; et al. (Elsevier, 2022)
Objectives: This study modified Healthy Eating Index (HEI) based on hemodialysis (HD)-specific nutritional guidelines and investigated associations between the diet quality (DQ) and nutritional risk in HD patients. Methods: The HD-HEI tool adapted the Malaysian Dietary Guidelines 2010 framework according to HD-specific nutrition guidelines. This HD-HEI was applied to 3-day dietary records of 382 HD patients. Relationships between HD-HEI scores and nutritional parameters were tested by partial correlations. Binary logistic regression models adjusted with confounders were used to determine adjusted odds ratio (adjOR) with 95% confidence interval (CI) for nutritional risk based on HD-HEI scores categorization. Results: The total HD-HEI score (51.3 ± 10.2) for this HD patient population was affected by ethnicity (Ptrend <.001) and sex (P =.003). No patient achieved “good” DQ (score: 81-100), while DQ of 54.5% patients were classified as “needs improvement” (score: 51-80) and remaining as “poor” (score: 0-51). Total HD-HEI scores were positively associated with dietary energy intake (DEI), dietary protein intake (DPI), dry weight, and handgrip strength, but inversely associated with Dietary Monotony Index (DMI) (all P <.05). Individually, scores for refined grain, total protein, and animal protein were positively associated with DEI (all P <.05), while total, animal, fish, and vegetable proteins indicated positive associations with DPI (all P <.05). Moderating metrics for convenience meals, saturated fats, sodium, and fluid negatively correlated toward DEI with similar trends for DPI excepting convenience meals and fluids. “Poor” DQ was associated with DMI ≥ 29.2 (adjOR 18.83, 95% CI 9.36-37.86, P <.001), Malnutrition Inflammation Score ≥ 5 (adjOR 1.78, 95% CI 1.01-3.15, P =.045), and protein energy wasting (adjOR 1.96, 95% CI 1.14-3.34, P =.031), but became nullified with covariate adjustments. “Poor” DQ was also associated with low lean tissue mass (<32.6 kg) in men (adjOR 2.38, 95% CI 1.01-5.58, P =.046) but not women. Conclusion: “Poor” DQ was associated with poor nutritional status in Malaysian HD patients, who should be targeted for nutritional counseling.